Managerial Discretion - Wangrow, David B.; Schepker, Donald J.; Barker, Vincent L. (Journal of Management, 2015)
Scholars have long been interested in when and to what degree managers are able to exert control over their organizations. In this review, we examine managerial discretion, or the latitude of action available to managers. Since its introduction, scholars have attempted to explain when managers will have discretion, what discretion means for organizational outcomes, and how discretion may differentially influence organizational outcomes when it enables or constrains leaders. Our review indicates that while a significant number of studies have examined discretion, few have attempted to validate the prescriptions of the managerial discretion construct. Furthermore, studies to date have primarily focused on the industry task environment as a measure of discretion, with less attention focused on the manager’s characteristics and the internal organization. We then assess construct validity and the measurement of managerial discretion, offering recommendations to future researchers for improving the operationalization of this construct. Finally, we consider how discretion forces may interact as either complements or substitutes and how such interactions may have both organizational- and individual-level consequences.